Effect of Selenium on Control of Postharvest Gray Mold of Tomato Fruit and the Possible Mechanisms Involved - Wu, Zhilin; Yin, Xuebin; Bañuelos, Gary S.; Lin, Zhi-Qing; Zhu, Zhu; Liu, Ying; Yuan, Linxi; Li, Miao (Frontiers in Microbiology, 2016)
Selenium (Se) has important benefits for crop growth and stress tolerance at low concentrations. However, there is very little information on antimicrobial effect of Se against the economically important fungus Botrytis cinerea. In the present study, using sodium selenite as Se source, we investigated the effect of Se salts on spore germination and mycelial growth of the fungal pathogen in vitro and gray mold control in harvested tomato fruit. Se treatment at 24 mg/L significantly inhibited spore germination of the fungal pathogen and effectively controlled gray mold in harvested tomato fruit. Se treatment at 24 mg/L seems to induce the generation of intracellular reactive oxygen species in the fungal spores. The membrane integrity damage was observed with fluorescence microscopy following staining with propidium iodide after treatment of the spores with Se. These results suggest that Se has the potential for controlling gray mold rot of tomato fruits and might be useful in integrated control against gray mold disease of postharvest fruits and vegetables caused by B. cinerea. The mechanisms by which Se decreased gray mold decay of tomato fruit may be directly related to the severe damage to the conidia plasma membrane and loss of cytoplasmic materials from the hyphae.